The Implementation of Yana Arthashastra in The Indo-Pacific Region Through The AUKUS Agreement - Herlina Tria Sukmawati (UNIDA Gontor, 2024)
This article aims to explain the United States strategy in balancing China's dominance in the Indo-Pacific region through forming strategy balancing China's dominance in the Indo-Pacific region through the formation of the AUKUS alliance as a security pact in the Indo-Pacific area. The discussion in this article focuses on the US strategy to balance China's influence in the Indo-Pacific. To explain this problem, the author uses the Yana strategy, namely the foreign entitled Arthashstra. Yana's policy is the policy of being ready to attack. Yana's policies will later be linked to the values of the balance of power concept in modern international relations. Kautilya mentioned that peace and stability in a country strengthen it but never avoid attacks and war. Therefore, countries must be prepared to face war, which could occur at any time and the importance of alliances to safeguard their national interests. The author argues that AUKUS was a US strategy to reduce China's military influence in the region. This research uses qualitative methods with data collection techniques through literature study. The research results show that the US helping Australia develop the capability to build nuclear-powered submarines locally in Adelaide, which will strengthen Australia in the Indo-Pacific region, is a US strategy. Therefore, this strategy means that the US can avoid dealing with China, which could lead to confrontation. Through cooperation with Australia, the US can demonstrate its presence internationally to safeguard its national interests.